Winnie in winter : edition for learners of English - Thomas, Valerie; Paul, Korky (New York : Oxford University Press, 2008)
Tired of the cold and snow, Winnie the Witch casts a spell that changes winter into summer.
Keywords: Winnie the Witch (Fictitious character); Humorous stories; Witches -- Fiction